Financial centres in global financial networks: a quantitative analysis of investment banking deals - Pažitka, V (2018)
This thesis is structured around two primary objectives. First, to contribute to the literature on the world city network and the emerging literature on global financial networks by developing and empirically testing a new methodological approach for modelling urban networks that would aid the development of empirical research in these related streams of literature. Second, to provide empirical evidence showing the effects of positioning within global financial networks on individual financial services firms as well as financial centres. To achieve these objectives, this thesis first develops a novel modelling approach for empirical analysis of urban networks, which draws on the concept of underwriting syndicate as the primary building block of global financial networks. It also considers the consequences of the network boundary specification problem in the context of studying urban networks and compares the modelling approach it develops to the Interlocking World City Network Model (Taylor, 2001) and Alderson and Beckfield (2004) ownership ties approach. The empirical analysis that follows relies on data on investment banking deals sourced from Dealogic databases. The dataset built for the purposes of this thesis spans the 1993 – 2016 period and covers more than 1 million capital market transactions worldwide. To achieve the second objective of this thesis, I have built spatial econometric and dynamic panel data models to uncover the effects of positioning within GFNs on individual financial services firms and financial centres. The results of this thesis indicate that inter-cluster network ties that connect financial services firms located in different financial centres are particularly valuable and they benefit both the performance of individual firms and lead to higher resilience of financial centres to demand shocks. In contrast, localised network connections are not found to be statistically significant in either context. Given the interdisciplinary nature of this thesis, its methodological developments and empirical findings, it contributes to several related groups of literature, including the research on the world city network, global financial networks, underwriting syndicates and social network analysis. The implications of this thesis for public policy and corporate strategy relate primarily to the role of network connectivity in financial sector and the distinct role of syndication networks. I specifically relate this to contemporary issues including BREXIT, which as I discuss may have a material impact on the financial sector in the United Kingdom and beyond.